Nephropathy in Hypertensive Animals Is Linked to M2 Macrophages and Increased Expression of the YM1/Chi3l3 Protein. (10th July 2019) - Cavalcante, Paula Andréa Malveira; Alenina, Natalia; Budu, Alexandre; Freitas-Lima, Leandro Ceotto; Alves-Silva, Thaís; Agudelo, Juan Sebastian Henao; Qadri, Fatimunnisa; Camara, Niels Olsen Saraiva; Bader, Michael; Araújo, Ronaldo Carvalho
Abstract : Macrophages contribute to a continuous increase in blood pressure and kidney damage in hypertension, but their polarization status and the underlying mechanisms have not been clarified. This study revealed an important role for M2 macrophages and the YM1/Chi3l3 protein in hypertensive nephropathy in a mouse model of hypertension. Bone marrow cells were isolated from the femurs and tibia of male FVB/N (control) and transgenic hypertensive animals that overexpressed the rat form of angiotensinogen (TGM(rAOGEN)123, TGM123-FVB/N). The cells were treated with murine M-CSF and subsequently with LPS+IFN- γ to promote their polarization into M1 macrophages and IL-4+IL-13 to trigger the M2 phenotype. We examined the kidneys of TGM123-FVB/N animals to assess macrophage polarization and end-organ damage. mRNA expression was evaluated using real-time PCR, and protein levels were assessed through ELISA, CBA, Western blot, and immunofluorescence. Histology confirmed high levels of renal collagen. Cells stimulated with LPS+IFN- γ in vitro showed no significant difference in the expression of CD86, an M1 marker, compared to cells from the controls or the hypertensive mice. When stimulated with IL-4+IL-13, however, macrophages of the hypertensive group showed a significant increase in CD206 expression, an M2 marker. The M2/M1 ratio reached 288%. Our results indicate that when stimulated in vitro, macrophages from hypertensive mice are predisposed toward polarization to an M2 phenotype. These data support results from the kidneys where we found an increased infiltration of macrophages predominantly polarized to M2 associated with high levels of YM1/Chi3l3 (91, 89%), suggesting that YM1/Chi3l3 may be a biomarker of hypertensive nephropathy.